State Regulation of the Tourism Industry for Attracting International Investment - SHAYAKHMETOVA, Liliya; MAIDYROVA, Aigul; MOLDAZHANOV, Marat (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020, 2020)
The possibilities of developing the tourism industry in the Republic of Kazakhstan based on attracting investment and public-private partnerships (PPP) are examined in this article. The goal of the study is to analyze the possibilities of investing in the tourism industry of Kazakhstan with due consideration of the risk component and to determine the main strategic directions for the development of the tourism industry in Kazakhstan. The authors have analyzed the tourism regulatory practice in the Republic of Kazakhstan and identified the main problems of the tourism industry. The analysis has indicated that the large territory of the country, underdevelopment of the tourism infrastructure, and unwillingness of the tourism business to invest in its development are high-risk factors that require more global investment in the development of the tourism industry. The development of the tourism industry is supposed to be carried out with the comprehensive state support through the creation of a special system of legislative acts and favorable conditions for attracting investment and developing infrastructure. The approaches to attracting investment in various areas of the tourism industry, adopted by the leadership of various countries, have been considered. The authors have proposed recommendations for improving legislative measures and measures of state support for the tourism industry in Kazakhstan, primarily those that should secure the investment flows, based on the analysis of international experience and practice of the tourism industry in Kazakhstan. The issue of attracting international investment to the tourism industry in PPPs has been considered separately. The conclusions and proposals made on the basis of the research results can be used in the regulatory activities of specialized state bodies, taken into account when making investment decisions, and used as educational and methodological materials in the study of state regulation of tourism.